2019
DOI: 10.1186/s12931-019-1212-x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cell conditioned media for lung disease: a systematic review and meta-analysis of preclinical studies

Abstract: BackgroundInflammation plays an important role in the pathogenesis of many lung diseases. Preclinical studies suggest that mesenchymal stromal cell (MSC) conditioned media (CdM) can attenuate inflammation. Our aim was threefold: (1) summarize the existing animal literature evaluating CdM as a therapeutic agent for pediatric/adult lung disease, (2) quantify the effects of CdM on inflammation, and (3) compare inflammatory effects of CdM to MSCs.MethodsAdhering to the Systematic Review Protocol for Animal Interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Remarkably, preclinical studies suggest MSC conditioned media (CdM) may be as restorative as the MSCs themselves [22,23]. We supported this observation in a previous systematic review and meta-analysis demonstrating that CdM is as effective as MSCs in modulating inflammation [24].…”
Section: Introductionsupporting
confidence: 80%
“…Remarkably, preclinical studies suggest MSC conditioned media (CdM) may be as restorative as the MSCs themselves [22,23]. We supported this observation in a previous systematic review and meta-analysis demonstrating that CdM is as effective as MSCs in modulating inflammation [24].…”
Section: Introductionsupporting
confidence: 80%
“…Interestingly, the systematic review indicated that, unlike MSCs, their conditioned media do not improve the PH (88). A similar conclusion was drawn from another systematic review of preclinical studies that used MSCconditioned media for various lung diseases (129). Only two studies (89, 90) on experimental BPD met the criteria for inclusion in these analyses.…”
Section: Stem Cells and Their Conditioned Mediasupporting
confidence: 52%
“…Emukah et al [72] conducted a systematic review on the effects of mesenchymal stromal cell conditioned media (CdM) on many lung diseases. The findings were enthusiastic because it was demonstrated that CdM improved inflammation and was as effective as MSCs.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…The findings were enthusiastic because it was demonstrated that CdM improved inflammation and was as effective as MSCs. Further studies must be conducted to determine the ideal site of CdM delivery, dosage, and timing of the treatment according to the lung disease [ 72 ]. Zhao et al [ 73 ] also conducted a systematic review and meta-analysis evaluating the safety of cell therapies and the clinical variables critical for these lung disorders.…”
Section: Clinical Trialsmentioning
confidence: 99%